Fantastic Four. Vol. 3, The impossible is probable - North, Ryan, 1980- (Marvel Worldwide Inc., 2024)
"The Fantastic Four meet the Jurassic Four! When our FF swap places with a set of bizarre alternate-reality counterparts, they find themselves battling for survival...in a world where everyone is a dinosaur! Meanwhile, one year ago, Reed Richards sent the entire city block on which the Baxter Building stands - along with his own children and the children of his best friends Ben and Alicia - one year ahead in time. It was a desperate measure, but it saved them. And now we're finally catching up with them! Plus: A revenge plot like nothing you've ever seen! The First Family's kids make up for lost time! Susan Storm, archaeologist, makes a shocking find! The new S.H.I.E.L.D. takes shape! And, at last, Franklin Richards' secret is revealed! Collecting FANTASTIC FOUR (2022) #12-17." --